The SIMPLIFY Protocol: A Monophasic Extraction System Suitable for Exposomics, Metabolomics, Lipidomics, and Proteomics Research - Nguyen, Anh Hoang; Castro-Alves, Victor; Holmström, Flores Emilia; Barbosa, João Marcos G.; Kråkström, Matilda; Reinivuori, Päivikki; Kauko, Otto; Dickens, Alex; Orešič, Matej; Hyötyläinen, Tuulia (American Chemical Society (ACS), 2026)
Advancing our understanding of human health and disease requires comprehensive analytical approaches capable of capturing the complex interplay between endogenous metabolism and environmental exposures. A major challenge in clinical research is the ability to capture multidimensional data, particularly a broad range of biochemical profiles, due to limitations of biological resources, time, and budget. In this study, we introduce the SIMPLIFY Protocol, a unified monophasic extraction method that enables the simultaneous extraction of chemical exogenous products and endogenous molecules. The method was evaluated against in-house extraction techniques, including protein precipitation with methanol (MeOH) and acetonitrile (ACN), and the Folch method using various sample types, particularly certified reference materials. We demonstrate that the SIMPLIFY Protocol not only performs comparably to our in-house methods but also offers enhanced versatility for additional applications such as derivatization and proteomics. The analyte abundances and reproducibility with this method strongly correlate with those from in-house-established techniques across diverse sample types. The method encompasses a broad spectrum of compounds, effectively profiling approximately 800 identified compounds, including polar compounds (e.g., amino acids), semipolar compounds (e.g., polyfluorinated compounds, bile acids, and lysophophatidylcholine), and nonpolar compounds (e.g., cholesteryl ester), with some limitations in extracting triacylglycerols. By maintaining simplified workflow and minimizing biological and resource consumption of multiple extractions, this method supports high-throughput exposomics/metabolomics and lipidomics studies. Furthermore, its streamlined design facilitates (semi)automation, making it highly suitable for large-scale clinical studies, where efficiency, cost-effectiveness, and sample availability are critical factors.